Novel host-related virulence factors are encoded by squirrelpox virus, the main causative agent of epidemic disease in red squirrels in the UK. - Alistair C Darby; Colin J McInnes; Karina Hansen Kjær; Ann R Wood; Margaret Hughes; Pia Møller Martensen; Alan D Radford; Neil Hall; Julian Chantrey (PLoS ONE, 2014)
Squirrelpox virus (SQPV) shows little evidence for morbidity or mortality in North American grey squirrels (Sciurus carolinensis), in which the virus is endemic. However, more recently the virus has emerged to cause epidemics with high mortality in Eurasian red squirrels (S. vulgaris) in Great Britain, which are now threatened. Here we report the genome sequence of SQPV. Comparison with other Poxviridae revealed a core set of poxvirus genes, the phylogeny of which showed SQPV to be in a new Chordopoxvirus subfamily between the Molluscipoxviruses and Parapoxviruses. A number of SQPV genes were related to virulence, including three major histocomaptibility class I homologs, and one CD47 homolog. In addition, a novel potential virulence factor showing homology to mammalian oligoadenylate synthetase (OAS) was identified. This family of proteins normally causes activation of an endoribonuclease (RNaseL) within infected cells. The putative function of this novel SQPV protein was predicted in silico.